The use of the methods of the lower squares and the smaller squares weighted in the estimation of the parameters and design of the sample acceptance schemesFor general exponential distribution - عبود سهيل نجم (Journal of Economics and Administrative Sciences, 2011)
The acceptance sampling plans for generalized exponential distribution, when life time experiment is truncated at a pre-determined time are provided in this article. The two parameters (α, λ), (Scale parameters and Shape parameters) are estimated by LSE, WLSE and the Best Estimator’s for various samples sizes are used to find the ratio of true mean time to a pre-determined, and are used to find the smallest possible sample size required to ensure the producer’s risks, with a pre-fixed probability (1 - P*). The result of estimations and of sampling plans is provided in tables. Key words: Generalized Exponential Distribution, Acceptance Sampling Plan, and Consumer’s and Producer Risks